Crystal plasticity based investigation of micro-void evolution under multi-axial loading conditions. (June 2020) - Guo, He-Jie; Ling, Chao; Busso, Esteban P.; Zhong, Zheng; Li, Dong-Feng
Abstract: The present work investigates the effects of stress state and crystallographic orientation of the principal stress axes on the growth behaviour of micro-voids embedded in an aluminium alloy single crystal. Cubic unit cells with a spherical void located at their centre are relied upon to study the behaviour of the porous FCC single crystal under multiaxial loading conditions. A physics-based crystal plasticity constitutive model is used to describe crystallographic slip around the voids. Special emphasis is placed on quantifying the ductile behaviour of the porous material, where the description of the stress state requires the use of two dimensionless parameters: the stress triaxiality and the so-called Lode parameter. A detailed investigation is carried out to study the effect of the crystallographic orientation of the principal stress axes for a given stress state on the behaviour of the voided single crystal. The results show that the Lode parameter has a strong effect on single crystal void growth at low triaxialities, as well on void coalescence strains. A general relation is proposed to determine the void coalescence strain, a measure of the material ductility, in terms of a novel equivalent loading parameter which depends, in turn, on the stress state and the relative orientation of the principal stress axes. A transitional state has been identified from void failure mechanism maps where neither void collapse nor void coalescence occurs when the stress state in the porous single crystal varies from high to low triaxialities. Highlights: The effect of the crystallographic orientation of the principal stress axes on the behaviour of the voided single crystal. A general relation proposed to determine the void coalescence strain in terms of a novel equivalent loading parameter. A transitional state between void collapse void coalescence identified from void failure mechanism maps.